1984
DOI: 10.1111/j.1365-2125.1984.tb04990.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to theophylline in chronic bronchitis.

Abstract: In chronic bronchitis, intersubject variability in both theophylline pharmacokinetics and pharmacodynamics must be taken into account if the drug is to be used to its best advantage. Both kinds of variability can be integrated into a model which relates the steady state concentration of theophylline to simultaneously measured ventilatory response (most conveniently, the FVC). In a group of 56 patients with chronic bronchitis, the mean +/- s.d. linear response to increasing steady state concentrations of theoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The Bayesian method can be applied in clinical practice by using a number of computer programs [8][9][10][11][12]. Among these, the ADVISE program [12], designed for the Hewlett-Packard HP-85/87 microcomputer, is one of the most commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The Bayesian method can be applied in clinical practice by using a number of computer programs [8][9][10][11][12]. Among these, the ADVISE program [12], designed for the Hewlett-Packard HP-85/87 microcomputer, is one of the most commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in obtaining a serum theophylline level >10 µg·mL -1 in the long-term treatment of reversible airway obstruction is well-known, because of the difficulties in using this drug [14]. However, the therapeutic benefit of theophylline in treating airways obstruction is dose-related, and can be observed at levels as low as 5 µg·mL -1 , particularly when theophylline is given in conjunction with β 2 -agonists [15,16]. In our study, only nine subjects in the theophylline group showed a serum theophylline concentration <5 µg·mL -1 at the end of the active treatment, suggesting that compliance with the treatment was acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that in some studies no parameters for a concentration-effect relationship are given, [30] while others have used a linear concentration-effect modeU 31,32] It can therefore only tentatively be concluded that the EC so for bronchodilation is 10 to 15 mg/L.…”
Section: Theophyllinementioning
confidence: 97%